The effect of selective quinoa varieties (Chenopodium quinoa willd.) on in vitro rumen fermentation and methane production - Ewa Pecka-Kiełb; Bożena Króliczewska; Barbara Król; Maja Słupczyńska; Józef Sowiński; Andrzej Zachwieja; Jowita Kaszuba; František Zigo (Journal of Applied Animal Research)
The study compared the effects of three quinoa varieties, Titicaca (QA), Vikinga (QB), Zeno (QC) with those of other regularly used forages: whole wheat crop (WWC), alfalfa forage (AF), mixed grass forage (FG), on in vitro gas production, methane (CH4) emission, pH, volatile fatty acid concentrations, utilization index, and fermentation efficiency factor using cow rumen fluid. The fermentation of 1 g of WWC, AF, FG, QA, QB, or QC substrates was conducted in vitro under anaerobic conditions using the ANKOM RF system. Compared to QC, AF increased (p < 0.05) acetic acid proportion. The butyric acid proportion was the highest with QA and QC, the latter not differing from QB. The butyric acid proportion was the lowest with AF, followed by FG and WWC. When QC was used as a substrate in rumen fluid, it produced less cumulative gas and CH4 (p < 0.05) than WWC and QA without affecting total volatile fatty acid (VFA) concentration. The study provides physiological support for the use of Zeno quinoa as a nutritious roughage feed alternative for cows as well as shows that quinoa has no negative effects on fermentation, and can be used in cow feed as a replacement for dried feed.